Hell's corner - Baldacci, David; McLarty, Ron.; Cassidy, Orlagh (New York : Hachette Audio, 2010)
A bomb detonates in the White House immediately after the British prime minister departs from the state dinner. Oliver Stone, who witnesses the event, believes the prime minister and the president were targets of a terrorist plot. MI-5 agent Mary Chapman is assigned to assist Stone and his Camel Club with the investigation, which reveals that the bombing may have actually been botched and is part of a darker, deadlier conspiracy.
Abridged.
Compact discs.
Read by Ron McLarty and Orlagh Cassidy.
Keywords: Stone, Oliver (Fictitious character) -- Fiction; Camel Club (Imaginary organization) -- Fiction; Bombing investigation -- Fiction; Washington (D.C.) -- Fiction; Suspense fiction; Audiobooks